2019
DOI: 10.31550/1727-2378-2019-161-6-47-52
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Modulation of Visual Brain Responses during Classical Conditioning in Patients with Recurrent vs. Bipolar Depressio

Abstract: Цель исследования: изучение различий в активности мозга у пациентов с депрессивным эпизодом в рамках рекуррентной (РД) и биполярной депрессии (БД). Дизайн: контролируемое нерандомизированное экспериментальное исследование. Материалы и методы. Выделены три группы: с РД (n = 16; 10 женщин), БД (n = 16; 8 женщин) и здоровых добровольцев (n = 16; 9 женщин). Группы пациентов с депрессией не получали лекарств и не различались по шкалам тревоги и депрессии Гамильтона. Испытуемые сортировали 160 фотографий людей и жив… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
2
0
2
Order By: Relevance
“…Для каждой из четырех категорий был свой ключпростая фигура. Более подробно стимулы и дизайн исследования описаны в наших работах [11,12].…”
Section: стимулы и общий план исследованияunclassified
See 1 more Smart Citation
“…Для каждой из четырех категорий был свой ключпростая фигура. Более подробно стимулы и дизайн исследования описаны в наших работах [11,12].…”
Section: стимулы и общий план исследованияunclassified
“…Топография ЭМ для двух групп контроля была схожей, у РДМ она не определялась, у РДЖ отличалась от нормы. Это соответствует полученным нами ранее результатам на смешанной группе пациентов [12].…”
Section: результаты и обсуждениеunclassified
“…Consequently, EEG parameters can be useful as biological markers of a mental illness that trace back to specific pathophysiological mechanisms. Data accumulated to date from high-caliber studies [10-12] , including the results of our own studies [13,14] , suggest various EEG markers that can be used to differentiate between unipolar and bipolar depression. However, the question of how well they hold up to scrutiny remains open.…”
Section: Introductionmentioning
confidence: 96%
“…According to some studies, the quantitative characteristics of the alpha rhythm can only be fully understood after one takes into account the spectral power and activation intensity (inhibition of the alpha rhythm after one opens their eyes, the Berger effect) [18,19] . Considerable data now exists on the changes that take place in the alpha power in depressive disorders of various origins [10-17] . However, only a few studies into the activation reaction in patients with depressive disorders can be found in the literature [20] .…”
Section: Introductionmentioning
confidence: 99%